Varicella Zoster-Induced Severe Diabetic Ketoacidosis - Asri Mukti Nanta; Agustia Sukri Ekadamayanti; Krishna Wardhana Sucipto; Hendra Zufry (PP PERKENI, 2025)
Diabetic ketoacidosis (DKA) is a life-threatening complication of diabetes. There are not many cases reported relate to this case. This case report aims to present a case of DKA which is a common and potentially life-threatening complication in T1DM and can be the first sign of undiagnosed diabetes. A 36-year-old female presented with altered mental status and breathing difficulty. The patient's three children had recently contracted varicella (chickenpox). The patient was diagnosed with type 1 diabetes mellitus 8 months ago, with irregular adherence to treatment. Vital signs included a blood pressure of 84/60 mmHg on norepinephrine at 12 mcg/min, heart rate of 135 bpm, respiratory rate of 33 breaths/min, and temperature of 38.9°C. Physical examination revealed multiple lenticular, circumscribed vesicles with an erythematous base across the entire body. Laboratory results showed leukocytosis (leukocytes: 16,000 x 103/μL), hyperglycemia (random blood glucose: 273 mg/dL), severe metabolic acidosis (pH: 7.002, HCO3: 5.7 mEq/L, BE: -23.6 mEq/L), hypoxemia (pO2: 38 mmHg, SaO2: 52.8%), hypoalbuminemia (albumin: 3.48 g/dL), and stage I acute kidney injury (creatinine: 1.36 mg/dL). Urinalysis revealed the presence of ketone bodies. The patient was subsequently diagnosed with severe diabetic ketoacidosis, varicella zoster infection, septic shock with multiorgan failure, and type 1 diabetes mellitus. Despite initial treatment efforts, the patient’s condition continued to deteriorate, with no signs of clinical improvement. After 3 days, the patient deceased. In conclusion, although varicella zoster infection is an uncommon precipitant of DKA, the present case report highlights the critical role of varicella zoster vaccination and optimal glycemic control in DMT1 to prevent infection-related DKA progression.